Establishing help-seeking pathways bereaved through perinatal death in Dr George Mukhari Hospital, Gauteng Province - Moloisane-Ledwaba, Johanna Mmasetla (My University, 2022)
The psychological impact of perinatal death in the form of bereavement has been widely researched especially from the western perspective. The aim of this study was to establish the help-seeking pathways by mothers bereaved through perinatal death from the African perspective. The qualitative research paradigm in particular the phenomenological approach was adopted for the study. Phenomenology is described as an approach that focuses on the study of the lived experiences of individuals within their world. The application of this approach included personal interviews of 20 mothers who have experienced perinatal death at Doctor George Mukhari hospital in Gauteng province. The aim was to establish the help-seeking pathways they adopted to relief their distress, in terms of how they managed their bereavement and the help that they sought to relief their emotional distress. The findings of the study indicated that mothers lacked knowledge about what precipitated the onset of sudden symptoms such as early rupture of membrane, bleeding, lack of foetal movement which finally led to perinatal death. This lack of knowledge led mothers to attribute the cause of perinatal death to various reasons and conclusions such as distance decay, bad roads that delayed their arrival timeously at the hospital for their babies to be saved. Some cited lack of sense of urgency from the medical personnel and shortage of staff, especially doctors. However, they perceived positive social support from their families, spouses and medical professionals as one of the factors that contributed to their level of calmness and ability to bear the pain of loss. However, participants sought alternative help to facilitate clear understanding about what could have caused their babies to die, also how to manage their grief and how to deal with their subsequent pregnancies. Most of the participants benefited from the various healing pathways they chose. There is a need for healthcare system and community support to be more responsive to the plight of bereaved mothers, in reducing the stigma and the self-blame by bereaved mothers by offering support through counseling center. The findings reaffirm that despite the great studies taken in reducing perinatal deaths, there is a need for collaboration between the modern healthcare system and the traditional healthcare practitioners. Furthermore, emphasis v is needed on the preventative measures and training of healthcare practitioners within the maternal and child healthcare system to further reduce the alarming increase of prenatal deaths
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2022
Keywords: Bereavement; Mothers; Still births; Prenatal deaths; Perinatal death; Stillbirth; Pregnant women; Hospitals; Perinatal death -- Psychological aspects